Probing the Facilitation of International (Chinese) Adult Students’ Multi-fold Transformation: A Qualitative Approach - Fujuan Tan (Adult Education Research Conference, 2014)
This paper uses in-depth interviews to investigate the important role of instructors in the process of multi-fold transformation for international Chinese students who come to study in the U.S.